2009
DOI: 10.1051/0004-6361/200811471
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the chemical evolution of a collapsing prestellar core in two spatial dimensions

Abstract: Context. The physical conditions in a collapsing cloud can be traced by observations of molecular lines. To correctly interpret these observations the abundance distributions of the observed species need to be derived. The chemistry in a collapsing molecular cloud is not in a steady state as the density and temperature evolve. We therefore need to follow chemical reactions, both in the gas phase and on dust grains, as well as gas-grain interactions, to predict the abundance distributions. Aims. Our aim is to m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 83 publications
3
27
0
Order By: Relevance
“…The resulting chemical stratification significantly complicates the interpretation of molecular line observations, and again requires the use of sophisticated chemical models which have to be coupled to the dynamical evolution (e.g. Aikawa et al, 2008;van Weeren et al, 2009;Furuya et al, 2012). From the observational side, the freeze-out of many molecules makes it difficult to use their emission lines for probing the physical conditions in the inner regions of the cores.…”
Section: Chemical Stucturementioning
confidence: 99%
“…The resulting chemical stratification significantly complicates the interpretation of molecular line observations, and again requires the use of sophisticated chemical models which have to be coupled to the dynamical evolution (e.g. Aikawa et al, 2008;van Weeren et al, 2009;Furuya et al, 2012). From the observational side, the freeze-out of many molecules makes it difficult to use their emission lines for probing the physical conditions in the inner regions of the cores.…”
Section: Chemical Stucturementioning
confidence: 99%
“…Roberts et al 2007;Semenov et al 2010;van Weeren et al 2009). In terms of this model it can be described as a porous layer, fully exposed to surface reactions.…”
Section: Formation Of the Mantlementioning
confidence: 99%
“…Nilsson et al (2000) have shown, however, that this ratio depended on multiple factors, time evolution being only one of them, and other conditions such as the initial O/C + ratio would strongly influence the result making the SO/CS ratio an unreliable clock if the other parameters cannot be estimated with some accuracy. The existence of chemical clocks has not yet been established (van Weeren et al 2009) but the situation is now evolving: we recently presented a chemical model that clearly constrains the age of molecular clouds below 10 My (Pagani et al 2011).…”
Section: Introductionmentioning
confidence: 99%